INTERNALISASI KARAKTER TOLERANSI BERAGAMA DALAM TRADISI MASYARAKAT MUSLIM KUNCI - Mulat, Tri (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This research is motivated by the rise of intolerance cases both domestically and internationally, which often trigger conflicts due to differences in opinion, ethnicity, culture, and religion. Religion is the most vulnerable factor in causing social conflict, threatening national unity, violating humanitarian principles, and harming many parties. Awareness of the importance of tolerance is key to preventing potential conflicts and maintaining communal peace. The purpose of this study is to explore and describe the process of internalizing the value of religious tolerance within the traditions of the Muslim community of Kunci, which has practiced it in a concrete way as a model for living in harmony, mutual respect, and preserving social cohesion. This research applies a field study method with a qualitative approach, using observation, interviews, and documentation. Observation is used to obtain factual data about daily tolerance practices, while interviews aim to gather in-depth information from religious leaders, traditional leaders, village officials, elders, and community members. The study was conducted from January to March 2025 and analysed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that tolerance internalization occurs through value transformation, value transaction, and trans-internalization, supported by individual awareness, a conducive environment, stakeholder support, and adequate facilities, but hindered by globalization, differences in religious understanding, extremism, and fanaticism.